Implementasi Penilaian Autentik dalam Pembelajaran PAI Materi Ibadah Haji di SD 19 Batuang Taba: Penelitian - Afifah ‘Ulya; Elfa Maijuana; Yusnil Khoiriah Siregar; Zainal Asril; Rozi Fitriza (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to analyse how authentic assessment is applied in learning Islamic Religious Education (PAI) about Hajj at SD 19 Batuang Taba. Authentic assessment is an evaluation approach to assess the extent of students' abilities through tasks that are the application of knowledge in real situations. In this research, we used a qualitative method with a case study approach. Data collection was conducted by observation and in-depth interviews with PAI teachers and students as well as analysing existing learning documents. The informants in this study were 2 PAI teachers and 30 fifth grade students of SD 19 Batuang Taba. The results of this study indicate that authentic assessment in the Hajj material has been implemented through various instruments, such as performance assessment, portfolio, and project assessment. The learning activities implemented include simulation of Hajj rituals, making a mock-up of the Kaaba as well as directly explaining the pillars and conditions of Hajj. The findings show an increase in students' understanding of concepts by 85% and applicative skills by 78%. However, there are still obstacles related to limited infrastructure and the need for continuous teacher training. This study recommends developing more varied authentic assessmentinstruments and increasing teacher capacity inimplementation.